3rd URV Doctoral Workshop in Computer Science and Mathematics - Valls Mateu, Aïda; Gómez Jiménez, Sergio (Congressos, 2016)
This proceeding book contains the contributions presented at the 3rd URV Doctoral workshop in Computer Science and Mathematics, held in November 2016. The main aim of this workshop is to promote the dissemination of the ideas, methods and results that are developed by the students of our PhD program.